Tantangan Kritis dalam Pemungutan Pajak Sarang Burung Walet untuk Peningkatan Pendapatan Daerah di Kabupaten Ketapang - Yanti, Mauliani Harva; Ibrahim; Luqman (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
The swallow's nest tax in Ketapang Regency holds substantial potential for boosting regional income, yet faces obstacles. This research identifies and analyzes issues in tax collection, focusing on the local government's efforts to maximize revenue. Using qualitative methods with a case study approach, primary data was collected through interviews, complemented by secondary data on local regulations, tax policies, and swallow's nest production statistics. Findings reveal: 1) Tax collection, as per Law No. 28 of 2009 (10% of selling price), is not burdensome but faces a Rp. 173 million leakage due to inadequate supervision by Bapenda during shipping. 2) Swallow's nest tax contributes 12.5% to Regional Revenue (PAD), ranking third in 2023 after BPHTB and MBLB. 3) Collection challenges include insufficient socialization, taxpayer awareness, ineffective supervision, and human resource competence. 4) Government efforts involve socialization, education, improved supervision during shipping, and enhanced human resource competence, especially in production estimation. Swallow's nest tax has regional development and community welfare potential, viewed positively in Ketapang Regency, with an Islamic perspective considering it mandatory charity (shodaqoh), indicating a significant contribution to regional development.